Abjection and violence in Monoceros, by Suzette Mayr - Schneider, Liane (Acta Scientiarum. Language and Culture, 2015)
Through the analysis of Monoceros (2011), a novel by Canadian contemporary writer Suzette Mayr, we examine the entanglement between concepts of violence and abjection in literature. Mayr presents several characters that come into contact as a result of a suicide committed by a previously bullied student of a Catholic school. With the narrative as a reference, we propose to discuss the growing violence inside the school system in contemporary times, in this case as a result of sexual intolerance. Works by Nan Stein and Melinda York, who address the imposition of too strict gender roles on female and male students as one of the causes for violent outcomes among youngsters, will be our main theoretical references. We also discuss the topic of desire and abjection, mainly developed by Kristeva and Kulzbach, as illuminating perspectives for the analysis of the selected novel. We suggest that in Monoceros bullying is performed to guarantee fixed and binary models of gender identity, which ends up by promoting low self-esteem and feelings of awkwardness on individuals defined as different from the norm.